Investigating Transfer Motivation Profiles, Their Antecedents and Transfer of Training - Bastian de Jong; Joost Jansen in de Wal; Frank Cornelissen; Thea Peetsma (MDPI AG, 2023)
Despite investments of companies in employee trainings, transfer of training remains low. One component influencing transfer is transfer motivation. Recent insights have shown that different components of transfer motivation possibly independently influence transfer of training. It is therefore possible that transfer motivation profiles can be distinguished. However, it is unclear whether such motivational profiles exist. In this study, we investigated motivational profiles, how these profiles differ in antecedents influencing transfer motivation and how these profiles differ in transfer intention and transfer of training. This study does so by using the unified model of task-specific motivation (UMTM). Data were collected among 1317 participants who filled in a questionnaire representing the UMTM components directly after the training and indicated transfer after six weeks. Outcomes showed that four transfer motivation profiles could be distinguished, labeled: 'very optimistic', 'moderately optimistic', 'personal value' and 'conscious'. Moreover, profiles scoring higher on motivational components scored higher on antecedents of transfer motivation, transfer intention and transfer of training. These outcomes suggest that trainings and work circumstances need to be tailored differently toward different trainees to raise their transfer motivation and transfer of training.